1966
DOI: 10.1042/bj1000775
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic and peptidase activities of the jejunum and ileum of the rat during postnatal development

Abstract: 1. Proteolytic (substrate nitrocasein), tripeptidase (substrate glycylglycylgly-cine) and aminopeptidase (substrate leucyl-beta-naphthylamide) activities were studied in homogenates of jejunal and ileal mucosa of 7-, 10-, 14-, 21-, 35- and 60-day-old rats. 2. Proteolytic activity was practically the same in jejunum of 7-, 10-, 14- and 21-day-old rats, but after day 21 a significant increase was observed. The activity of the ileum changed very little during postnatal development and was always higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1968
1968
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 11 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…The oligoaminopeptidase and the y-glutamyltranspeptidase are the only brush border peptidases whose developmental pattern has been studied in human (4,18), rat (26), and guinea pig (8) intestine.…”
Section: Speculationmentioning
confidence: 99%
“…The oligoaminopeptidase and the y-glutamyltranspeptidase are the only brush border peptidases whose developmental pattern has been studied in human (4,18), rat (26), and guinea pig (8) intestine.…”
Section: Speculationmentioning
confidence: 99%
“…Although the development of several enzymes associated with intraluminal or intramucosal protein digestion has been studied [22], these enzymes are all specific for cr carboxyl-amide-linked peptides. The present report concerns the presence of a different type of intestinal peptidase, GGTP, which hydrolyzes only y carboxyl-amide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The postnatal development of many pep tidase activities such as enterokinase [30], leucylnaphthylamidase [25] and tripeptidase (substrate glycylglycylglycine) [28] have been established in different intestinal segments in rats and mice. In the proximal part of the small intestine of suckling rats, Raul et al [30] have reported that enterokinase reaches its maximum activity during the 2nd week after birth, then declines towards the adult values which are established during the 4th week.…”
Section: Discussionmentioning
confidence: 99%
“…After completion of incubation at 37 °C, the activity was stopped in the reaction tubes by the addition of 1 ml of 20% acetic acid in water. In the second step of y-GT assay, the Bratton and Marshall reactions by means of which the released p-nitroanilide gives a purple color in the presence o f N-naphthylethylcne-diamine was used [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation